Transformer-Capsule Model for Intent Detection (Student Abstract) - Obuchowski, Aleksander; Lew, Michał (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
Intent recognition is one of the most crucial tasks in NLU systems, which are nowadays especially important for designing intelligent conversation. We propose a novel approach to intent recognition which involves combining transformer architecture with capsule networks. Our results show that such architecture performs better than original capsule-NLU network implementations and achieves state-of-the-art results on datasets such as ATIS, AskUbuntu ,and WebApp.